Directly Including Data with Alzheimer's Publications Through Augmented Reality and Web Technologies – Schol‐AR. (20th December 2022) - Ard, Tyler; Bienkowski, Michael S; Pa, Judy; Contreras, Joey A; Sepehrband, Farshid; Yan, Lirong; Toga, Arthur W.
Abstract: Background: Alzheimer's disease research is multi‐disciplinary by nature and based on many forms of data, from MRI scans to microscopic image stacks. Much of this information is difficult to communicate through standard scientific articles and figures, often resulting in incomplete data reporting and suboptimal comprehension for many readers. Method: We introduce a community‐accessible data layering approach for directly including modern digital information on top of scientific figures, enabling entire datasets to be included with scientific articles. Through this approach readers can easily view data associated with publications through mobile devices or web browsers, averting the need to simplify complex data into 2D static figures. Result: Data layering facilitates communication and comprehension of Alzheimer's research by enabling accessible viewing of complex information directly with scientific articles, posters, and other formats. Conclusion: Using augmented reality and web technologies we can modernize communication of Alzheimer's research, bridging the gap between the digital basis of modern science and the natural limitations of journal articles.